(untitled) (Castilla. Estudios de Literatura, 2018)
This work intends to analyze the chronicle Jornadas Náuticas by Fray Jacinto de Carvajal in the light of the Bajtian concepts chronotope and polyphony, in dialogue with the history surrounding the events narrated by the chronicle. This reading of Fray Jacinto’s text demonstrates both a vision of time marked by the Christian-Catholic tradition, and an experience of space characterized by daily practices, the amazing nature and ethnographic records. The chronotope allows us to understand how polyphony evidences voices with unique features, which make the natives autonomous and resistant to the Spanish arrival.